Integrasi Akuntansi dan Edukasi Gizi dalam Program Pengabdian Masyarakat: Studi Kasus Desa Pusu, Kabupaten Timor Tengah Selatan - Lois Damaris Mone Ly; Maria Yunita Wea Folo; Maria Ansila Bere; Cornelia Fransiska Slaka Pationa; Linny Elvita Sari Adu; Eusabius Seda Woga; Maria Natalia Golan Leton; Don Oscar Filius Sae; Sesilia Pahat; Skolastika Saga Bengu; Maria Stefania Dea Kaka; Rivany Fabiola Nahak Abrantes; Maria Angela Witni Tilik; Maria Yasinta Kurniati Jehamu; Kristina Wada Betu (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Stunting remains a serious challenge in many rural areas, including Pusu Village, Amanuban Barat Sub-district, South Central Timor Regency. The lack of parental knowledge regarding childcare, balanced nutrition, environmental sanitation, and household resource management are dominant factors that exacerbate the nutritional condition of children under five. This Community Service Program through the Student Community Service aims to improve the knowledge, skills, and awareness of the community in preventing stunting through educational, participatory approaches, as well as the integration of household accounting aspects. The methods implemented included initial observation, community education, diffusion of science and technology, training, family assistance, advocacy, and evaluation. The target group consisted of 30 families with children aged 0–5 years, selected purposively based on their vulnerability to stunting. Education was provided through nutrition and health counseling, training on local food-based meal preparation, and the practice of simple household financial recording. Family mentoring and mediation with village officials were also conducted to ensure program sustainability. The results showed a significant improvement in mothers’ knowledge of balanced nutrition, hygiene practices, and skills in managing household finances. Behavioral changes were reflected in the increased variety of family food consumption, the practice of handwashing with soap, and the adoption of household expenditure records. The integration of simple accounting practices also assisted families in allocating resources more effectively for children’s nutritional needs. In conclusion, this PKM program successfully created a positive impact on stunting prevention efforts in Pusu Village. Future initiatives require continuous monitoring and community-based program strengthening to ensure that the interventions become more effective and sustainable.